Effects of candesartan cilexetil and amlodipine orotate on receptor for advanced glycation end products expression in the aortic wall of Otsuka Long-Evans Tokushima Fatty (OETFF) type 2 diabetic rats - Kang, Min-Kyu; Chung, Woo-Baek; Hong, Seul-Ki; Kim, Ok-Ran; Ihm, Sang-Hyun; Chang, Kiyuk; Seung, Ki-Bae (Archives of pharmacal research, 2016)
The receptor for advanced glycation end products (RAGE) plays a key role in the development of vascular inflammation and acceleration of atherosclerosis in type 2 diabetes. We investigated the effect of candesartan cilexetil (CDRT) and amlodipine orotate (AMDP) on the expression of RAGE in the aortic walls of Otsuka Long-Evans Tokushima Fatty (OLETF) rats and AGE-treated endothelial cells. Twenty five-week-old OLETF rats were randomized to 8 week treatments consisting of CDRT (n = 8), AMDP (n = 8) or saline (control, n = 8). Immunohistochemical and dihydroethidine staining revealed reduced RAGE and reactive oxygen species (ROS) signals in rats treated with CDRT or AMDP compared with control rats. Both CDRT and AMDP suppressed the expression of p22phox and p47phox NADPH oxidase subunits. However, only CDRT significantly reduced expression of phosphorylated extracellular signal regulated kinase (pERK)1/2 in the aortic wall of OLETF rats. In addition, both drugs reduced RAGE expression and total and mitochondrial ROS production in the AGE-treated endothelial cells. Both ARBs and CCBs reduced RAGE expression in the aortic walls of OLETF rats, which was attributed to decreased ROS production through inhibition of NADPH oxidase. In addition, only CDRT reduced aortic expression of RAGE via suppression of the ERK1/2 pathway unlike AMDP.